Uji Aktivitas Sitotoksik Senyawa Analog 3,4-Diklorokalkon terhadap Sel Hela secara MTT - Nuraini Harmastuti; Muhammad Muchalal (Jurnal Farmasi Indonesia, 2014)
Chalcones has been known to have many biological activities, for example as an antitumour. These research synthesized and observed the cytotoxicity effects against HeLa cells of the 3,4- dichlorochalcone analog compound. These compounds were synthesized by modifying in the aromatic ring which attached at β position to the keton carbonyl. The aromatic ring was furanylaromatic. Synthesis of 3,4-dichlorochalcone analog compound was carried out by Vogel method using starting materials of furanylbenzaldehide and 3,4-dichloroacetophenone. These purity test of synthesized compound was analyzed using thin layer chromatography, melting range, and GC methods. Structure elucidation was determined by using physical methods, such as UV spectrophotometer, IR spectrophotometer, H1-NMR spectrometer, and MS spectrometer analysis. The compound was then observed the cytotoxicity effects against HeLa cells by MTT method. The result indicated that the 3,4-dichlorochalcone analog compound had been able to be synthesized, purified, and it had structure as a predicted compound, furanyl-3’,4’-dichlorochalchone. The cytotoxic results shown that the 3,4-dichlorochalcone analog compound with the IC50 value of 23,5 μg/ml.